Практичні аспекти застосування аутсорсингу на підприємствах машинобудування - Прохоренко, Олена Вікторівна (НТУ "ХПІ", 2015)
В статті наведено результати практичного застосування на машинобудівному підприємстві комплексного організаційно-економічного механізму управління аутсорсингом. Процес охоплює всі стадії, починаючи з виникнення проблеми, визначення бізнес-процесів в системі, матричної оцінки кожного з процесів і обрання типової стратегії бізнес-процесу; проектування відносин з контрагентом, оцінку і вибір потенційного контрагента, прогнозування ефективності і контроль результатів.

The article presents the results of practical use in the manufacture of machinery complex organizational and economic mechanism of outsourcing. The process covers all stages, starting with the problem, the definition of business processes in the system, each matrix evaluation process and the election of a typical business process strategies; design relationship with the contractor, assessment and selection of potential counterparty prediction efficiency and control results. Outsourcing management in the company provides a number of processes: the process of assessment and planning appropriate default strategy; organizing relations with the future contractor and adaptation processes of the organization, monitoring implementation. Outsourcing at the enterprise JSC «KTZ» showed the validity and effectiveness of the proposed methodological principles.
Practical aspects of outsourcing in the mechanical engineering
Keywords: механізм управління аутсорсінгом; бізнес-процеси; матричні оцінки; прогнозування; mechanism of outsourcing; business processes; communication policy; strategic planning